Chemical Composition, Antitumor Potential, and Impact on Redox Homeostasis of the Essential Oils of Orlaya grandiflora from Two Climate Localities - Vukic, Milena D.; Obradovic, Ana D.; Vukovic, Nenad L.; Kačániová, Miroslava; Djurdjevic, Predrag M.; Djelic, Gorica T.; Matic, Milos M. (Molecules (Basel, Switzerland), 2022)
It is well known that abiotic components can affect biosynthetic pathways in the production of certain volatile compounds. The aim of this study was to compare the chemical composition of essential oils obtained from Orlaya grandiflora (L.) Hoffm. collected from two localities in Serbia (continental climate, OG1) and Montenegro (Mediterranean climate, OG2) and to assess their antitumor potential on the human colon cancer HCT-116 and breast cancer MDA-MB-231 cell lines. EOs obtained by hydrodistillation were analyzed using GC-MS and GC-FID methods. The results indicate considerable differences in the chemical compositions of the two samples. Although in both samples the main class of volatiles observed was sesquiterpenes (47.5% for OG1 and 70.1% for OG2), the OG1 sample was characterized by a high amount of monoterpene hydrocarbons (29.3%), and sesquiterpene germacrene D (29.5%) as the most abundant compound. On the other hand, the OG2 sample contained a high quantity of oxygenated sesquiterpenes (20.6%), and β-elemene (22.7%) was the major constituent. The possible antitumor mechanisms of these EOs in the HCT-116 and MDA-MB-231 cell lines were examined by means of cell viability, apoptosis, redox potential, and migratory capacity. The antiviability potential appeared to be dose dependent, since the results showed that both EOs decreased the viability of the tested cells. Stronger antitumor effects were shown in MDA-MB-231 cells after short-term treatment, especially at the highest applied concentration, where the percentage of viability was reduced by over 40%. All tested concentrations of EOs exhibited proapoptotic activity and elevated activity of caspase-3 in a dose- and time-dependent manner. The results also showed decreased concentrations of superoxide anion radical in the treated cells, which indicates their significant antioxidative role. Long-term treatments showed mild recovery effects on cell viability in both cell lines, probably caused by the balancing of redox homeostasis. Elevated levels of nitrites indicate high levels of nitric oxide (NO) production and suggest its higher bioavailability due to the antioxidative environment. The tested EOs also induced a drop in migratory capacity, especially after short-time treatments. Taken together, these results suggest considerable antitumor activity of both EOs, which could have potential therapeutic applications.